Evaluation of composite resin microleakage with using different bonding agents by micro computed tomography - Binar Khalis Bilal; Diyar Khalid Bakr (Erbil Dental Journal)
Background and objectives: Microleakage is the major challenge in resin-based restorations. The aim of the study was to determine the amount of the microleakage for different adhesive systems with micro computed tomography. Material and methods: Thirty extracted human premolars have been used, by preparing standardized class V cavities. Thirty premolars divided into 3 groups of each 10 specimens. In group A; One up bond F plus, Tokuyama dentals (6th generation), group B; Palfique bond, Tokuyama dentals (7th generation), and group C; Palfique universal bond, Tokuyama dentals (8th generation) adhesive systems have been used. Palfique LX5, Tokuyama dentals composite resin used for restoration of cavities. After the specimens undergone thermocycling process (1000 cycles), immersed into the silver nitrate solution after the specimens being varnished by nail polish. Micro computed tomography scanning done for each specimen. Statistical analysis undergone by using descriptive statistic, one-way ANOVA and least significant difference (LSD) tests. Results: Group C; Palfique universal bond (8th generation) showed the least amount of microleakage followed by group B; Palfique bond (7th generation) adhesive systems; while group A; one up bond F plus (6th generation) adhesive system showed maximum amount of microleakage. Furthermore, there was a significant difference between group A; one up bond F plus (6th generation) and group; C Palfique universal bond (8th generation) adhesive systems. Conclusion: Newer adhesive systems have better success achievements and recommended to be used in practical bases.